Neuroticism and fear of COVID-19 during the COVID-19 pandemic: Testing the mediating role of intolerance of uncertainty and sense of control among Chinese high school students - Zhang, Donghuan; Fan, Min; Meng, Lingyi; Zheng, Xifu (Frontiers in Psychology, 2022)
Since the COVID-19 pandemic broke out in 2019, neuroticism has been proven a predictor of fear of COVID-19 infection. However, only few studies have been conducted on the factors affecting the relationship between neuroticism and this kind of fear. The present study is aimed at analyzing the role intolerance of uncertainty (IU) and sense of control (SOC) play in relation to neuroticism and the fear of COVID-19. We conducted a cross-sectional study in Guangdong and Guangxi provinces, China, and we collected complete datasets from 792 high school students. The main results can be described as follows: (a) individuals with high neuroticism tended to have higher intolerance of uncertainty (IU) and a lower sense of control (SOC); (b) IU and SOC played a mediating role between neuroticism and fear of COVID-19, and a serial mediation effect was found between these factors; (c) after controlling for both IU and SOC, the effect of neuroticism on fear was no longer significant. The results suggested a critical role of IU and sense of control in the causal relationship between neuroticism and fear.